The Clinicopathological Correlations of hTERC Amplification with Esophageal Squamous Cell Precursor Lesions - Hu, Yanping (Dig Dis Sci, 2018)
BACKGROUND: Esophageal squamous cell precursor lesions remain one of the most controversial topics in pathology and clinical management. AIMS: To analyze the dysregulation of human telomerase RNA component (hTERC) in esophageal squamous cell precursor lesions and the clinicopathological correlations with the characteristics of esophageal squamous cell precursor lesions. METHODS: Florescence in situ hybridization was performed to detect hTERC amplification in different gradings of esophageal squamous cell precursor lesions. With retrospective follow-up data, clinicopathological correlations between hTERC and esophageal squamous cell precursor lesions were subjected to logistic regression analysis. RESULTS: hTERC amplification gradually increased with upgrading of dysplasia, reaching the highest level in high-grade intraepithelial neoplasia, and there was a significant difference between the low-grade intraepithelial neoplasia group and the high-grade intraepithelial neoplasia group (P = 0.00). Logistic regression analysis showed that hTERC amplification was correlated with both dysplasia grading and ulcer characteristics of esophageal squamous cell precursor lesions (P < 0.05). CONCLUSIONS: hTERC amplification with increasing grading of esophageal squamous cell precursor lesions and the presence of ulcer characteristics might provide an important molecular and pathological marker for the diagnosis and clinical prognosis of esophageal squamous cell precursor lesions, especially for those ambiguous cases with more divergence in classification.